Qur’anic Concept of An-Naum Subāta: Linguistic Study and Relevance to Human Detoxification - Ilham Habibullah; Rochmad Rochmad; Mahmud Rifaannudin; Muhammad Hafidz Syaputra Utama (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
Purpose – Sleep is a fundamental biological necessity recognized in both the Qur’an and contemporary scientific research. The Qur’an refers to sleep through the terms an-naum, denoting natural rest for physical and mental restoration, and subāt, describing deep and restorative sleep that temporarily suspends human activity. This study aims to analyze the terminological meanings of an-naum and subāt in the Qur’an and to examine their relationship with the human body’s detoxification process from the perspective of modern neuroscience. Design/methodology/approach – This study employs a qualitative library-based research design using descriptive-analytical methods. The analysis focuses on QS. Al-Furqān (25): 47 and QS. An-Naba’ (78): 9 through linguistic interpretation (i‘jāz bayānī) and scientific interpretation (i‘jāz ‘ilmī). Relevant literature in Qur’anic exegesis, sleep science, and neuroscience is critically examined to explore the correspondence between Qur’anic concepts and contemporary scientific findings. Findings – The study demonstrates a significant convergence between the Qur’anic concept of sleep and modern scientific understanding of sleep physiology. While an-naum reflects the general biological function of rest, subāt corresponds conceptually to the deep sleep phase, during which restorative processes and brain detoxification mechanisms are most active. The findings indicate that the Qur’an portrays sleep not only as a divine blessing and physiological necessity but also contains scientific indications that are consistent with contemporary explanations of neural recovery and metabolic waste clearance during deep sleep. Research implications/limitations – As a conceptual study based on literature analysis, the findings remain interpretive and have not been validated through empirical biomedical research. Future interdisciplinary studies involving Qur’anic scholarship, neuroscience, and sleep medicine are needed to further examine the proposed conceptual relationship. Originality/value – This study contributes to the growing field of Qur’an and science by integrating Qur’anic semantics with contemporary neuroscience. It offers a novel interpretation of an-naum and subāt as complementary concepts of sleep physiology, enriching the discourse on i‘jāz ‘ilmī while highlighting the importance of sleep quality for both physical and spiritual well-being.